2011
DOI: 10.1177/1948550611401043
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal Asymmetry in Interracial Interactions

Abstract: This study examined the role of Blacks' level of racial identification in understanding how Blacks and Whites behaved, both verbally and nonverbally, toward each other in interracial interactions. The more Blacks identified with their racial group, the more nonverbally friendly they behaved toward their White partners. Paradoxically, Whites behaved less nonverbally friendly toward Blacks who were strongly racially identified relative to those who were weakly identified. Thus, Blacks who tried the hardest in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In this culturally “default” situation, we observed the strongest tendency towards threat. The current results further highlight how threatening the expression of dual identity by ethnic minority-group members can be to members of majority groups (see Kaiser, Drury, Malahy, & King, 2011; Plaut et al, 2011). At the same time, our results reveal that this is not a static, automatic, response; this threat of dual identity can be turned into challenge by means of a relatively simple mindset manipulation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this culturally “default” situation, we observed the strongest tendency towards threat. The current results further highlight how threatening the expression of dual identity by ethnic minority-group members can be to members of majority groups (see Kaiser, Drury, Malahy, & King, 2011; Plaut et al, 2011). At the same time, our results reveal that this is not a static, automatic, response; this threat of dual identity can be turned into challenge by means of a relatively simple mindset manipulation.…”
Section: Discussionmentioning
confidence: 65%
“…In terms of her appearance and background information (e.g., her involvement in an Islamic organization), the interaction partner can be regarded as highly identified with her ethnic background. Given that interactions between majority-group members and minority-group members who are highly identified with their ethnicity tend to be difficult (Falomir-Pichastor & Frederic, 2013; Kaiser et al, 2011), it is even more important and interesting that, under the appropriate circumstances, these interactions can actually also lead to positive outcomes (positive challenge rather than threat).…”
Section: Discussionmentioning
confidence: 99%
“…This may have significant consequences because majority group members tend to hold more negative attitudes and use less inclusive language when evaluating highly identified minority group members (Kaiser & Pratt-Hyatt, 2009; Kaiser et al, 2011; Sellers & Shelton, 2003). Kaiser et al (2011) demonstrated when a Black individual appeared to be highly identified with being Black, White participants used less inclusive language when writing an essay about an interaction they had with a Black student. Negative evaluations of highly identified minority group members have been theorized to be a reaction from the majority group feeling threatened in regard to their own status legitimacy or believing highly identified minorities hold negative attitudes toward the majority group (Branscombe et al, 1999; Brewer, 2007; Kaiser & Wilkins, 2010; Johns et al, 2005).…”
Section: Categorization and Prototypicalitymentioning
confidence: 99%
“…Wilkins et al (2010) found that individuals who were perceived to be highly prototypical of their ethnic group were perceived to identify more strongly with their racial group compared to those who were perceived to be lowly prototypical. This may have significant consequences because majority group members tend to hold more negative attitudes and use less inclusive language when evaluating highly identified minority group members (Kaiser & Pratt-Hyatt, 2009; Kaiser et al, 2011; Sellers & Shelton, 2003). Kaiser et al (2011) demonstrated when a Black individual appeared to be highly identified with being Black, White participants used less inclusive language when writing an essay about an interaction they had with a Black student.…”
Section: Categorization and Prototypicalitymentioning
confidence: 99%
“…Prior work demonstrates that minority group members’ levels of identification with the group affect the way they are perceived by high-power group members (e.g., Kaiser & Pratt-Hyatt, 2009). Specifically, majority group members tend to have more negative attitudes toward highly identified minority group members (Kaiser & Pratt-Hyatt, 2009), demonstrate less friendly behaviors when interacting with them (Kaiser, Drury, Malahy, & King, 2011), and even use different language when describing future interaction with them (Kaiser, Drury, & Malahy, 2009, described in Kaiser & Wilkins, 2010). In line with these findings, it is possible that merely identifying as a feminist, rather than putting gender on the table, would lead to negative reactions.…”
Section: Speaker’s Categorization As a Feministmentioning
confidence: 99%